Bis(2-diphenylphosphinoxynaphthalen-1-yl)methane: transition metal chemistry, Suzuki cross-coupling reactions and homogeneous hydrogenation of olefins - Punji, Benudhar; Mague, Joel T.; Balakrishna, Maravanji S. (Dalton Transactions, 2006)
Transition metal complexes of bis(2-diphenylphosphinoxynaphthalen-1-yl)methane (1) are described. Bis(phosphinite) 1 reacts with Group 6 metal carbonyls, [Rh(CO)2Cl]2, anhydrous NiCl2, [Pd(C3H5)Cl]2/AgBF4 and Pt(COD)I2 to give the corresponding 10-membered chelate complexes 2, 3 and 5–8. Reaction of 1 with [Rh(COD)Cl]2 in the presence of AgBF4 affords a cationic complex, [Rh(COD){Ph2P(–OC10H6)(µ-CH2)(C10H6O–)PPh2-κP,κP}]BF4 (4). Treatment of 1 with AuCl(SMe2) gives mononuclear chelate complex, [(AuCl){Ph2P(–OC10H6)(µ-CH2)(C10H6O–)PPh2-κP,κP}] (9) as well as a binuclear complex, [Au(Cl){µ-Ph2P(–OC10H6)(µ-CH2)(C10H6O–)PPh2-κP,κP}AuCl] (10) with ligand 1 exhibiting both chelating and bridged bidentate modes of coordination respectively. The molecular structures of 2, 6, 7, 9 and 10 are determined by X-ray studies. The mixture of Pd(OAc)2 and 1 effectively catalyzes Suzuki cross-coupling reactions of a range of aryl halides with aryl boronic acid in MeOH at room temperature or at 60 °C, giving generally high yields even under low catalytic loads. The cationic rhodium(I) complex, [Rh(COD){Ph2P(–OC10H6)(µ-CH2)(C10H6O–)PPh2-κP,κP}]BF4 (4) catalyzes the hydrogenation of styrenes to afford the corresponding alkyl benzenes in THF at room temperature or at 70 °C with excellent turnover frequencies.

Ruthenium(II), copper(I) and silver(I) complexes of large bite bisphosphinite, bis(2-diphenylphosphinoxynaphthalen-1-yl)methane: Application of Ru(II) complexes towards the hydrogenation of styrene and phenylacetylene - Punji, Benudhar; Mague, Joel T.; Balakrishna, Maravanji S. (Journal of Organometallic Chemistry, 2006)
Ruthenium(II), copper(I) and silver(I) complexes of large bite bisphosphinite Ph2P{(-OC10H6)(μ-CH2)(C10H6O-)}PPh2 (1) are described. Reactions of bisphosphinite 1 with [Ru(η6-p-cymene)(μ-Cl)Cl]2 and RuCl2(PPh3)3 afford mono- and bis-chelate complexes [RuCl(η6-p-cymene){η2-Ph2P{(-OC10H6)(μ-CH2)(C10H6O-)}PPh2-κP,κP}]Cl (2) and trans-[RuCl2{η2-Ph2P{(-OC10H6)(μ-CH2)(C10H6O-)}PPh2-κP,κP}2] (3), respectively. Treatment of 1 with CuX (X = Cl, Br and I) furnish 10-membered chelate complexes of the type [Cu(X){η2-Ph2P(-OC10H6)(μ-CH2)(C10H6O-)PPh2-κP,κP}] (4, X = Cl; 5, X = Br; 6, X = I), whereas [Cu(MeCN)4]PF6 affords a bis-chelated cationic complex [Cu{η2-Ph2P(-OC10H6)(μ-CH2)(C10H6O-)PPh2-κP,κP}2][PF6] (7). Reaction between 1 and AgOTf produce both mono- and bis-chelated complexes [Ag{η2-Ph2P(-OC10H6)(μ-CH2)(C10H6O-)PPh2-κP,κP}(SO3CF3)] (8) and [Ag{η2-Ph2P(-OC10H6)(μ-CH2)(C10H6O-)PPh2-κP,κP}2][SO3CF3] (9), respectively; whereas the similar reaction of 1 with[Ag(OTf)PPh3] affords chelate complex of the type [Ag{η2-Ph2P(-OC10H6)(μ-CH2)(C10H6O-)PPh2-κP,κP}(PPh3)(SO3CF3)] (10). All the complexes were characterized by 1H NMR, 31P NMR, elemental analysis and mass spectrometry, including low-temperature NMR studies in the case of silver complexes. The molecular structures of 4 and 6 are determined by X-ray diffraction studies. Ruthenium complexes 2 and 3 promote catalytic hydrogenation of styrene and phenylacetylene with good turnover numbers.

Synthesis of neutral (PdII, PtII), Cationic (PdII), and water-induced anionic (PdII) complexes containing new mesocyclic thioether-aminophosphonite ligands and their application in the suzuki cross-coupling reaction - Punji, Benudhar; Mague, Joel T.; Balakrishna, Maravanji S. (Inorganic Chemistry, 2006)
Mesocyclic thioether−aminophosphonite ligands, {−OC10H6(μ-S)C10H6O−}PNC4H8O (2a, 4-(dinaphtho[2,1-d:1‘,2‘-g][1,3,6,2]dioxathiaphosphocin-4-yl)morpholine) and {−OC10H6(μ-S)C10H6O−}PNC4H8NCH3 (2b, 1-(dinaphtho[2,1-d:1‘,2‘-g][1,3,6,2]dioxathiaphosphocin-4-yl)-4-methylpiperazine) are obtained by reacting {−OC10H6(μ-S)C10H6O−}PCl (1) with corresponding nucleophiles. The ligands 2a and 2b react with (PhCN)2PdCl2 or M(COD)Cl2 (M = PdII or PtII) to afford P-coordinated cis-complexes, [{(−OC10H6(μ-S)C10H6O−)PNC4H8X-κP}2MCl2] (3a, M = PdII, X = O; 3b, M = PdII, X = NMe; 4a, M = PtII, X = O; 4b, M = PtII, X = NMe). Compounds 2a and 2b, upon treatment with [Pd(η3-C3H5)Cl]2 in the presence of AgOTf, produce the P,S-chelated cationic complexes, [{(−OC10H6(μ-S)C10H6O−)PNC4H8X-κP,κS}Pd(η3-C3H5)](CF3SO3) (5a, X = O and 5b, X = NMe). Treatment of 2a and 2b with (PhCN)2PdCl2 in the presence of trace amount of H2O affords P,S-chelated anionic complexes, [{(−OC10H6(μ-S)C10H6O−)P(O)-κP,κS}PdCl2](H2NC4H8X) (6a, X = O and 6b, X = NMe), via P−N bond cleavage. The crystal structures of compounds 1, 2a, 2b, 4a, and 6a are reported. Compound 6a is a rare example of crystallographically characterized anionic transition metal complex containing a thioether−phosphonate ligand. Most of these palladium complexes proved to be very active catalysts for the Suzuki−Miyaura reaction with excellent turnover number ((TON), up to 9.2 × 104 using complex 6a as a catalyst).

Group 11 metal complexes of mesocyclic thioether-aminophosphonites, (-OC10H6) - Punji, Benudhar; Mague, Joel T.; Balakrishna, Maravanji S. (European Journal of Inorganic Chemistry, 2007)
Group 11 metal complexes of the mesocyclic thioether aminophosphonites [-OC10H6(μ-S)C10H6O-]PNC4H8E {2a: E = O; 2b: E = NMe; IUPAC names: 4-(dinaphtho[2,1-d:1′,2′-g][1,3,6,2]dioxathiaphosphocin-4-yl)morpholine (2a), 1-(dinaphtho[2,1-d:1′,2′-g][1,3,6,2]dioxathiaphosphocin-4-yl)-4-methylpiperazine (2b)} are reported. Thioether aminophosphonites 2a and 2b react with CuX (X = Cl, Br, and I) in a 1:1 molar ratio to give the tricoordinate, dimeric complexes [{[{-OC10H6(μ-S)C10H6O-}PNC4H8E-κP]Cu(μ-X)}2] (4a: E = O, X = Cl; 4b: E = NMe, X = Cl; 5a: E = O, X = Br; 5b: E = NMe, X = Br; 6a: E = O, X = I; 6b: E = NMe, X = I), whereas with 2:1 molar ratios monomeric complexes of the type[{[-OC10H6(μ-S)C10H6O-]PNC4H8O-κP}2CuX] (7a: E = O, X = Cl; 7b: E = NMe, X = Cl; 8a: E = O, X = Br; 8b: E = NMe, X = Br; 9a: E = O, X = I; 9b: E = NMe, X = I) are obtained in excellent yield. The P,S-chelated cationic complexes[{[-OC10H6(μ-S)C10H6O-]PNC4H8E-κP,κS}2Cu]BF4 (10a: E = O; 10b: E = NMe) are obtained when 2a and 2b are treated with half an equivalent of [(MeCN)4Cu]BF4. Similarly, thesilver complexes [{[{-OC10H6(μ-S)C10H6O-}PNC4H8E-κP,κS]AgCF3SO3}2] (11a: E = O: 11b: E = NMe) and [{[-OC10H6(μ-S)C10H6O-]PNC4H8E-κP,κS}Ag(PPh3)]CF3SO3 (12a: E = O; 12b: E = NMe) are synthesized by the treatment of thioether aminophosphonites 2a and 2b with AgOTf and [Ag(PPh3)][OTf], respectively. Reactions of 2a and 2b with [AuCl(SMe2)] produce the simple monomeric gold(I) complexes [{[-OC10H6(μ-S)C10H6O-]PNC4H8E-κP}AuCl] (13a: E = O; 13b: E = NMe). The iodo derivatives [{[-OC10H6(μ-S)C10H6O-]PNC4H8E-κP}AuI] (14a: E = O; 14b: E = NMe) are obtained by the halide-exchange reaction of 13a and 13b with CuI at room temperature. The structures of complexes 5a, 7a, 8a, 13a, 13b, and 14a are confirmed by single-crystal X-ray diffraction studies. In all of these complexes, the sulfur atom in the mesocyclic ring shows coordinative interaction towards the phosphorus atom, and in 5a, 7a, 8a, and 14a towards the metal center as well. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007)

Highly air-stable anionic mononuclear and neutral binuclear palladium(ii) complexes for C−C and C−N bond-forming reactions - Punji, Benudhar; Mague, Joel T.; Balakrishna, Maravanji S. (Inorganic Chemistry, 2007)
The short-bite aminobis(phosphonite), PhN{P(−OC10H6(μ-S)C10H6O−)}2 (2), containing a mesocyclic thioether backbone is synthesized by either treating PhN(PCl2)2 with 2 equiv of thiobis(2,2‘-naphthol) or reacting chlorophosphite (−OC10H6(μ-S)C10H6O−)PCl (1) with aniline in the presence of a base. Treatment of 2 with an equimolar amount of Pd(COD)Cl2 in the presence of H2O affords a P−N−P-bridged and P,S-metalated binuclear complex, [PhN(P(−OC10H6(μ-S)C10H6O−)-κP)2Pd2Cl2{P(−OC10H6(μ-S)C10H6O−)(O)-κP,κS}2] (3), whereas the same reaction with 2 equiv of Pd(COD)Cl2 in the presence of H2O and Et3N produces the mononuclear anionic complex [{(−OC10H6(μ-S)C10H6O−)P(O)-κP,κS}PdCl2](Et3NH) (5). By contrast, reaction of 2 with 2 equiv of Pd(COD)Cl2 and H2O in the absence of Et3N gives the hydrogen phosphonate coordinated complex [{(−OC10H6(μ-S)C10H6O−)P(OH)}PdCl2] (4) which converts to the anionic complex in solution or in the presence of a base. Compound 2 on treatment with Pt(COD)X2 (X = Cl or I) afforded P-coordinated four-membered chelate complexes [PhN(P(−OC10H6(μ-S)C10H6O−)-κP)2PtX2] (6 X = Cl, 7 X = I). The crystal structures of compounds 2, 3, 5, and 7 are reported. Compound 3 is the first example of a crystallographically characterized binuclear palladium complex containing a bidentate bridging ligand and its hydrolyzed fragments forming metallacycles containing a palladium−phosphorus σ bond. All palladium complexes proved to be very good catalysts for the Suzuki−Miyaura and Mizoroki−Heck cross-coupling and amination reactions with excellent turnover numbers (TON up to 1.46 × 105 in the case of the Suzuki−Miyaura reaction).

O-2-Naphthyl diphenylthiophosphinate - Mague, Joel T.; Punji, Benudhar; Ganesamoorthy, Chelladurai; Balakrishna, Maravanji S. (Acta Crystallographica Section E-Crystallographic Communications, 2007)
The molecule of the title compound, C10H7OP(S)(C6H5)2 or C22H17OPS, exhibits distorted tetrahedral geometry about the P atom. The P=S bond of 1.9355 (4) Å is shorter than that found in Ph3P=S [1.950 (3) Å] because the replacement of one carbon on phosphorus by oxygen increases the effective electronegativity of the P atom, thereby enhancing pπ–dπ back-donation from a lone-pair orbital of the S atom.

Thioether-functionalized ferrocenyl-bis(phosphonite), Fe(C5H4)P(−OC10H6(μ-S)C10H6O−)2: synthesis, coordination behavior, and application in suzuki-miyaura cross-coupling reactions - Punji, Benudhar; Mague, Joel T.; Balakrishna, Maravanji S. (Inorganic Chemistry, 2007)
The thioether-functionalized metalloligand ferrocenyl-bis(phosphonite), Fe(C5H4PR)2 (4, R = −OC10H6(μ-S)C10H6O−) is synthesized in three steps starting from ferrocene, and its coordination behavior toward various transition-metal derivatives is described. The reactions of 4 with [Rh(CO)2Cl]2 or M(COD)Cl2 afforded the chelate complexes, cis-[Rh(CO)Cl{Fe(C5H4PR)2-κP,κP}] (5) or cis-[MCl2{Fe(C5H4PR)2-κP,κP}] (6, M = PdII; 7, M = PtII), respectively. However, treatment of 4 with CuX (X = Cl, Br, and I) produces binuclear complexes, [Cu2(μ-X)2(MeCN){Fe(C5H4PR)2-κP,κP}] (8, X = Cl; 9, X = Br; 10, X = I) where the sulfur atom on one side of the ligand is involved in a weak interaction with the copper center. Reaction of 4 with 1 equiv of Ag(PPh3)OTf gives the mononuclear chelate complex [Ag(OTf)PPh3{Fe(C5H4PR)2-κP,κP}] (11), whereas treatment with 2 equiv of AuCl(SMe2) produces the dinuclear gold complex [Au(Cl){Fe(C5H4PR)2-κP,κP}Au(Cl)] (12). The crystal structures of 10 and 12 are reported, where a strong metallophilic interaction is observed between the closed-shell metal centers. The palladium complex 6 catalyzes the Suzuki cross-coupling reactions of aryl bromides with phenylboronic acid with excellent turnover numbers (TON up to 1.36 × 105).

Copper (I) complexes of a thioether-functionalized short-bite aminobis(phosphonite) - Punji, Benudhar; Mague, Joel T.; Mobin, Shaikh M.; Balakrishna, Maravanji S. (Polyhedron, 2009)
Copper(I) complexes of short-bite aminobis(phosphonite), PhN{P(–OC10H6(μ-S)C10H6O–)}2 (1) have been synthesized. Reactions of 1 with an excess of CuX (X = Cl, Br, and I) afforded the ligand-bridged binuclear complexes, [PhN(PR-κP)2{Cu(μ-X)(MeCN)}2] (2, X = Cl; 3, X = Br; 4, X = I; R = –OC10H6(μ-S)C10H6O–), whereas treatment with 0.5 equiv. of [Cu(MeCN)4]PF6 produces the mononuclear bischelated cationic complex, [{PhN(PR-κP)2}2Cu](PF6) (5). Single crystal X-ray structures of complexes 3 and 4 are reported. Complex 3 shows strong π–π stacking interactions between the naphthyl moieties, whereas complex 4 shows ligand-supported Cu⋯Cu metallophilic interactions.

Large-bite bisphosphite, 1,3-C6H4OPOC10H6(μ-S)C10H6O2: synthesis, copper(I), and gold(I) complexes - Balakrishna, Maravanji S.; Kumar, Pawan; Punji, Benudhar; Mague, Joel T. (Journal of Organometallic Chemistry, 2010)
Large-bite bisphosphite ligand 1,3-C6H4{OPOC10H6(μ-S)C10H6O}2 (3), is obtained by reacting chlorophosphonite {OC10H6(μ-S)C10H6O}PCl (2) with resorcinol in the presence of triethylamine. Treatment of 3 with CuCl in 1:1 molar ratio produces a 1D-coordination polymer [CuCl{(–OC10H6(μ-S)C10H6O–)P(–OC6H4O–)P(–OC10H6(μ-S)C10H6O–)}-κP,κP]∞ (4) in good yield. Similar reaction of 3 with two equivalents of AuCl(SMe2) affords a dinuclear complex, [Au2Cl2{(–OC10H6(μ-S)C10H6O–)P(–OC6H4O–)P(–OC10H6(μ-S)C10H6O–)}-κP,κP] (5). Single crystal X-ray structures of the ligand 3 and the complexes 4 and 5 are reported. The gold complex 5 shows dimeric structure supported by strong Au···Au aurophilic interactions.